When Caesar was king : how Sid Caesar reinvented American comedy - Margolick, David (Schocken Books, 2025)
When Caesar Was King tells the story of Sid Caesar, television's first true star and the genius behind Your Show of Shows. David Margolick traces Caesar's meteoric rise, his struggles behind the scenes, and his eventual fall from the airwaves--while highlighting his lasting influence on comedy through protégés like Mel Brooks, Carl Reiner, and Neil Simon.